Hardware-software complex for the study of sedimentation processes in technical and biological suspensions of aggregating micro- and nanoparticles - Баранец, Виталия Александровна; Кизилова, Наталья Николаевна; Дацок, Олег Михайлович (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2019)
A new hardware-software complex is proposed for automatic registration, processing and analysis of sedimentation curves in technical or biological suspensions of aggregating micro- or nanoparticles to assess the aging index of the industrial fluids, the state of microbiological suspensions, or medical diagnostics. The complex includes a centrifuge to create an inhomogeneous field of forces that accelerate the settling process. Registration of the sedimentation curves as the height of the column of aggregates in the lower part of the sedimentation tube is carried out using optical sensors. The curves can be taken repeatedly with or without the addition of various substances. The proposed method was tested, and the correspondence of the values ​​of the 1-hour index of  erythrocyte sedimentation rate and the 10-minutes centrifuge test was confirmed on a large data set. A three-phase mathematical model of the suspension is developed. This model more accurately describes the dynamics of sedimentation processes compared to the two-phase model. Computer code for the curves processing and calculation of the indices characterizing the state of the suspension is developed. Based on this model a new index  is proposed to evaluate the state of suspension. It has advantages because it does not require bringing the test samples to the same concentrations. Using the mathematical model you can determine  and the rate of aggregation of suspension particles. As a result a rapid assessment of the aggregation ability of suspension which characterizes the "age" of technical suspension is possible. An example of the use of the complex to assess the indicator of aggregation of red blood cells in order to diagnose the presence of food or drug allergies is given.